Strength predictions of clear wood at multiple scales using numerical limit analysis approaches. (February 2018) - Li, Mingjing; Füssl, Josef; Lukacevic, Markus; Eberhardsteiner, Josef; Martin, Christopher M.
Highlights: Tsai-Wu failure criterion and periodic boundary conditions are implemented. Annual ring scale and clear wood scale of spruce are considered in calculations. Effective failure behaviours are obtained efficiently with small computational error. Numerical results agree well with experimental results at the clear wood scale. Abstract: This work aims at a new approach for understanding failure mechanisms and predicting wood strengths, which are strongly influenced by the complex hierarchical material system of wood. Thus, a mechanical concept, where different microstructural characteristics are incorporated, appears to be necessary, based on the division of wood into meaningful scales of observation. At each scale, effective strength properties are to be determined and a multiscale approach needs to be applied, for which conventional numerical methods appear to be inefficient. In this work, numerical limit analysis approaches are further developed and applied for the first time to wood, complementing conventional methods successfully at certain scales of observation in a multiscale 'damage' approach. Limit analysis belongs to the group of direct plastic analysis methods, focusing exclusively on the time instant of structural collapse, and delivering the ultimate strength. Compared with conventional numerical approaches that have previously been applied to wood, limit analysis approaches are much more stable and efficient. In this work, orthotropic failure criteria and periodic boundary conditions are implemented into both lower bound and upper bound numerical limit analysis formulations. As numerical results, effective failure surfaces are obtained at both annual ring scale and clear wood scale. A validation at clear wood scale indicates that this new approach is very promising.